8x-2(x+1)=2(3x-1)

Simple and best practice solution for 8x-2(x+1)=2(3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-2(x+1)=2(3x-1) equation:


Simplifying
8x + -2(x + 1) = 2(3x + -1)

Reorder the terms:
8x + -2(1 + x) = 2(3x + -1)
8x + (1 * -2 + x * -2) = 2(3x + -1)
8x + (-2 + -2x) = 2(3x + -1)

Reorder the terms:
-2 + 8x + -2x = 2(3x + -1)

Combine like terms: 8x + -2x = 6x
-2 + 6x = 2(3x + -1)

Reorder the terms:
-2 + 6x = 2(-1 + 3x)
-2 + 6x = (-1 * 2 + 3x * 2)
-2 + 6x = (-2 + 6x)

Add '2' to each side of the equation.
-2 + 2 + 6x = -2 + 2 + 6x

Combine like terms: -2 + 2 = 0
0 + 6x = -2 + 2 + 6x
6x = -2 + 2 + 6x

Combine like terms: -2 + 2 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4-t=3(t-1)-5 | | 2(b+1)-(3+b)=-3 | | (6Y+7)-(5+5y)=10 | | 5+(x-5)=x | | 16y-112+8y=4y-150 | | 3x-y=19 | | 1.7q-5.1-4.1q=-1.4Q-5.1 | | 11-2m-(-13+2n)= | | 11-2m(-13+2n)= | | 9x+3+4x+8=12x+3 | | 1n+5+1m-3n+8= | | 12222222+12=14 | | 1987+1495= | | 40m*25m*2m= | | (3d+7)-d+5=2d+12 | | 4+6(x-3)=-38 | | 9+3y=3(3+y) | | 1.5(2x-4)=.5(x+3)-4 | | A=45 | | 5(3a-7)-9=46 | | 2.15x-4.63=x+1.19 | | 4x(x)(x)-25x=0 | | 5-2(x+3)+2= | | 4(2a-6)-8=46 | | 3(2y+6)=12 | | (5y-6)=7(2-4y) | | (4x)(4x)(4x)-25x=0 | | 2+5x-x^2= | | 19.55=8.5 | | 7(5y-6)=2-4y | | 3x-6=5x+15-4 | | x^2-x=132 |

Equations solver categories